(untitled) (Research, Society and Development, 2020)
The study aimed to identify the difficulties and coping of pregnant women and seropositive mothers in relation to society, verifying their understanding of the forms of transmission and treatment and the perception related to their quality of life. It deals with an integrative review. The search was carried out by two reviewers, simultaneously and independently, from March to April 2020. Thus, an active search was carried out in the databases registered in the electronic portal of the Virtual Health Library (VHL), where they are located. indexed the databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval Sistem online (MEDLINE), Nursing Database (BDENF); and in the Scientific Electronic Library Online (SciELO) virtual library, after analyzing the articles, 15 were selected for the study. The descriptors selected for the operationalization of the searches will be inserted in the vocabularies Descriptors in Health Sciences (DeCS) and in the Medical Subject Headings (MeSH), which were crossed are: Pregnancy found 1455 articles, HIV that were 85 articles and Pregnant Women 6 articles, totaling after the selection, reading in 15 articles for analysis and discussion of the research.This study allowed to understand the perception of the pregnant women and puerperal women in relation to HIV, where many show sadness and despair when they worry about prejudice and often with a lack of information.